Case report: Serotoninergic and cholinergic syndromes induced by self-medication - Sofía Orozco-Solano; Martha Milena Silva-Castro; Manuel Machuca (Frontiers Media S.A., 2023)
Self-medication is a part of the self-care practices carried out by the elderly in their environment. The aim of this case report is to show how the self-medication of fluoxetine and dimenhydrinate in an older adult can induce serotoninergic and cholinergic syndromes, showing symptoms such as nausea, tachycardia, tremor, loss of appetite, memory loss, decreased vision, falls, and increased urination. An older adult who has been diagnosed with arterial hypertension, dyslipidemia, diabetes mellitus, and a recent diagnosis of essential thrombosis is the subject of this case report. After the analysis of the case, cessation of fluoxetine was recommended to avoid withdrawal symptoms, therefore decreasing the need for dimenhydrinate and the medicines used for dyspepsia. After the recommendation, the patient showed an improvement in the symptoms. Finally, the comprehensive evaluation process of the medication in the Medicines Optimization Unit achieved the detection of the problem and improved the patient's health condition.